Hybrid solving algorithms for an extended dynamic constraint satisfaction problem based configuration system - Wang, Lin (2013)
In modern manufacturing, constraint satisfaction problem based product configuration systems have been recognized as an effective and promising approach to represent and solve product family design tasks. In this article, based on an extended dynamic constraint satisfaction problem based product configuration system, a hybrid constraint satisfaction problem solving algorithm with forward checking and backjumping with fail-first heuristic is proposed. To control backtracking occurrence in this hybrid solving algorithm when new active variables are introduced into dynamic constraint satisfaction problem, a hybrid heuristic (a combination of an amended most-constrained heuristic and fail-first heuristic) is integrated with forward checking and backjumping for better solution efficiency. Experiments on both algorithms have been performed on a dynamic constraint satisfaction problem based PC configuration task.